l logarithmof500

Evaluate the following logarithmic expression

logarithmof500

Evaluate logof500

You didn't enter a base

We'll do bases e and 2-10

Evaluate loge(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = e and x = 500, we have:

loge(500)  =  Ln(500)
  Ln(e)

Ln(e) = 1

loge(500) = 6.2146080984222

Evaluate log2(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 2 and x = 500, we have:

log2(500)  =  Ln(500)
  Ln(2)

log2(500) = 8.9657842846621

Evaluate log3(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 3 and x = 500, we have:

log3(500)  =  Ln(500)
  Ln(3)

log3(500) = 5.6567800692967

Evaluate log4(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 4 and x = 500, we have:

log4(500)  =  Ln(500)
  Ln(4)

log4(500) = 4.482892142331

Evaluate log5(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 5 and x = 500, we have:

log5(500)  =  Ln(500)
  Ln(5)

log5(500) = 3.8613531161468

Evaluate log6(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 6 and x = 500, we have:

log6(500)  =  Ln(500)
  Ln(6)

log6(500) = 3.4684388195809

Evaluate log7(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 7 and x = 500, we have:

log7(500)  =  Ln(500)
  Ln(7)

log7(500) = 3.1936768002568

Evaluate log8(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 8 and x = 500, we have:

log8(500)  =  Ln(500)
  Ln(8)

log8(500) = 2.988594761554

Evaluate log9(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 9 and x = 500, we have:

log9(500)  =  Ln(500)
  Ln(9)

log9(500) = 2.8283900346483

Evaluate log10(500) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 10 and x = 500, we have:

log10(500)  =  Ln(500)
  Ln(10)

log10(500) = 2.698970004336

Final Answer


loge(500) = 6.2146080984222
log2(500) = 8.9657842846621
log3(500) = 5.6567800692967
log4(500) = 4.482892142331
log5(500) = 3.8613531161468
log6(500) = 3.4684388195809
log7(500) = 3.1936768002568
log8(500) = 2.988594761554
log9(500) = 2.8283900346483
log10(500) = 2.698970004336